Pengoptiman Pendapatan Lahan Parkir Kendaraan Bandar Udara Internasional Lombok Menggunakan Metode Branch & Bound - Siti Rahmatullah; Mamika Ujianita Romdhini; Marwan Marwan; Lailia Awalushaumi (Universitas Islam Negeri (UIN) Mataram, 2012)
In this research, integer linear programming of vehicle’s setting in Lombok International Airport is solved by Branch and Bound Method. Branch and Bound is the method that can deliver integer solution of the linear programming. The optimum result is parking area’s income of Lombok International Airport can be achieved until Rp1.218.690.000/month with lade of 384 unit’s of motorcycle, 990 units of class I of the car, and 21 units of the bus or truck with the length < 9 m. If we make a comparison between the maximum income with the number of tax in number Rp90.074.550, then the number of the tax is only 7,31% of the maximum income. So that, in the other words we can say that the number of tax which accepted by Central Lombok’s Government is not representative with parking area’s income which can be acquired.